Essays on the economics of education - Shakya, Prasiddha, author; Miller, Ray, advisor; Zahran, Sammy, advisor; Pena, Anita Alves, committee member; Magnan, Nicholas, committee member (Colorado State University. Libraries, 2025)
This dissertation comprises three empirical studies that investigate how educational policies and disruptions influence student outcomes across K–12 and higher education contexts in the United States. The first chapter examines the impact of New Jersey's "$50K The First Day" policy, which established a $50,000 minimum salary for new teachers. Using school-level panel data and a staggered difference-in-differences design under a continuous treatment framework, I show that this salary floor increased teacher pay across the board and led to measurable improvements in student academic performance, including proficiency gains in mathematics and English Language Arts (ELA), as well as modest increases in graduation and college enrollment rates. The second chapter turns to postsecondary education and evaluates the Bridge Scholars Program (BSP), a pre-college summer initiative aimed at supporting first-generation and low-income students at a large public land-grant university in the United States. Employing a fuzzy regression discontinuity design within a local randomization framework, I find that BSP increases first-year and second-year persistence, with suggestive evidence that non-financial program components—such as mentoring and peer support—are central to its effectiveness. The final chapter explores how the COVID-19 pandemic, and the associated transition to remote instruction, affected undergraduates' retention in and transition into STEM fields. Employing a staggered difference-in-differences approach with student-level longitudinal data, I explore both persistence within STEM majors and switching behavior into and out of STEM and Biology/Health-related majors. Contrary to early concerns, I find little evidence of significant or lasting disruption to students' field-of-study decisions. Taken together, these studies contribute to ongoing policy conversations around teacher compensation, college access and retention, and the postsecondary consequences of the pandemic—a major educational disruption. Each chapter offers evidence-based insights that I hope can be used for designing interventions that promote student success and equity.
Keywords: education policy; teacher labor market; higher education; economics of education